Association of endoscopic variceal treatment with portal venous system thrombosis in liver cirrhosis: a case–control study. (May 2022) - Wang, Le; Guo, Xiaozhong; Shao, Xiaodong; Xu, Xiangbo; Zheng, Kexin; Wang, Ran; Chawla, Saurabh; Basaranoglu, Metin; Qi, Xingshun
Background: The association of endoscopic variceal treatment (EVT) with portal venous system thrombosis (PVST) in liver cirrhosis is still unclear. Methods: PVST was assessed by contrast-enhanced CT or MRI in 406 cirrhotic patients from our prospective database. Case and control groups, which are defined as patients with and without PVST, respectively, were matched at a ratio of 1:1 according to age, gender, Child-Pugh class, and MELD score. History of EVT was reviewed. Logistic regression analysis was used to identify the risk factors for PVST. Odds ratios (ORs) were calculated. Subgroup analyses were further performed in terms of degree and location of PVST. Results: Overall, 109 patients each were included in case and control groups. The case group had a significantly higher proportion of patients who had undergone EVT than the control group (53.2% versus 18.3%; p < 0.001). In detail, the case group had significantly higher proportions of patients who had undergone EVT for controlling bleeding (45.9% versus 14.7%; p < 0.001), endoscopic variceal ligation (EVL) alone (19.3% versus 9.2%; p = 0.033), and EVL combined with endoscopic cyanoacrylate glue injection (24.8% versus 5.5%; p < 0.001). EVT was independently associated with PVST (OR = 4.258; p < 0.001). In subgroup analyses, EVT remained independently associated with partial PVST (OR = 10.063; p < 0.001), complete PVST/fibrotic cord (OR = 4.889; p = 0.008), thrombosis within main portal vein (OR = 5.985; p < 0.001), and thrombosis within superior mesenteric and splenic veins (OR = 5.747; p < 0.001). Conclusions: EVT may lead to a higher risk of PVST, especially more severe PVST, in liver cirrhosis. Screening for and prophylaxis of PVST after EVT should be further explored.